Exploring the English language teachers’ beliefs and practices in implementing CEFR aligned formative assessment in Malaysian primary schools / Hanisah Mohd Yunus, Lilliati Ismail and Abu Bakar Mohamed Razali - Mohd Yunus, Hanisah; Ismail, Lilliati; Mohamed Razali, Abu Bakar (Academy of Language Studies, 2023)
The adoption of the CEFR undeniably leads to changes in curriculum, teaching and learning, as well as assessment. Changes in curriculum requires changes in teachers’ practices and this demand puts strain on teachers as it requires them to change their practice and resume the role of “novice” again. This study explored English language teachers’ beliefs about CEFR-aligned formative assessment and their classroom practices in the Malaysian primary school context. This study employed an explanatory sequential quantitative-driven design. In this design, the researcher collected data through two questionnaires, namely the Assessment Beliefs Questionnaire and the Assessment Practice Questionnaire. A cluster random sampling was used to collect data from 134 teachers at 30 selected schools in Selangor. The data was analysed using descriptive analysis (frequency, percentage, mean and standard deviation) and inferential analysis (Pearson Moment Correlation Coefficient) using Statistical Package for the Social Science (SPSS) version 25. Findings of this study indicated that teachers held positive perceptions of formative assessment and these positive perceptions are reflected in their practices.